Drawing: A novel approach to understanding appearance change in people following treatment for head and neck cancer. (June 2019) - Harding, Sam; Bradford, John
Objectives: Appearance is a factor within head and neck cancer health-related quality of life measures; however, the issue of self-perceived appearance has received scant attention. Self-portraiture may provide insight into the patient's perspective, allowing people to provide viewpoints that are not easily accessible. This research investigates the methodology of drawing and responses from patient-completed questionnaires in a head and neck cancer population. Methods: A sample of 30 people at least 3 months post-treatment for head and neck cancer were recruited. Participants completed the Derriford Appearance Scale, University of Washington Quality of Life scale, and two drawings: (1) how they recall themselves pre-treatment and (2) how they see themselves post-treatment. They were asked to discuss the methodology and their experience of it. Results: Correlations with Derriford Appearance Scale, University of Washington Quality of Life scale, and size drawings failed to find relationships between these variables. Post-treatment drawings were significantly smaller than pre-treatment. Qualitative analysis of the drawings found differences between the images. Participants related how drawing gave an opportunity to voice concerns that questionnaires and clinic appointments did not. Conclusion: Drawing can elicit distinctly different information about a person following treatment for head and neck cancer than that provided by health-related quality of life measures. Further research would clarify if clinical opinion matches patients' drawing.